METAMORFOSIS “ILLAT HUKUM” DALAM SAD ADZ-DZARI’AH DAN FATH ADZ-DZARIAH (SEBUAH KAJIAN PERBANDINGAN) - Baroroh, Nurdhin (Al-Mazaahib: Jurnal Perbandingan Hukum, 2017)
Sad Adz-Dzariah is a breakthrough method produced by the scholars of Usul Fikih to protecting and keeping the human being as Mukallaf falling or rubbing on damage or mafsadah by closing and blocking all means, tools and wasilah that will be used for some action. But as a result of the development of life, there is another aspect that should be of concern as opposed also to avoiding damage or Mafsadah, namely the realization of the benefit or Jalbu al-Maslahah, by opening and allowing to use the means, tools and or wasilah that will be used for some action, by another method of ijtihad Fath Adz-Dzariah. So that the next concern is on the logical link or 'Illat Law must also be seen again for use, so then the transition from the Sad Adz-Dzariah Method to the Fath Adz-Dzariah Method can be done.Kata Kunci: Sad Adz-Dzariah, Fath Adz-Dzariah, sarana, alat dan wasilah